Hybrid Ag@Rice Leaf Biochar Nanocomposite As Photocatalyst For Efficient Degradation Of Methylene Blue And Denaturation Of Micro-Organisms - Nworie, Felix; Frank, Nwabue; Meashack, Elom; Clinton, Oroke; Boniface, Oke; Nkechi, Eze; IkeAmadi, Chioma (Andalasian International Journal of Applied Science, Engineering and Technology, 2024)
Organic-inorganic hybrid nanocomposite is currently in the fore front of research because it is ecofriendly, safe, cost effective, methodologically facile and effective for the removal of methylene blue (MB) from aqueous solution. In this study, hybrid Ag@rice leaf extract/rice leaf biochar nanocomposite (Ag@RLEBN) was hydrothermally fabricated for the degradation of MB and denaturation of microorganisms. To understand the mechanisms between Ag@RLEBN and MB/microorganism, the physicochemical analysis, reusability, photocatalytic degradation parameters and microbial inhibition diameter were investigated. The obtained results revealed Ag@RLEBN as face centered cubic crystalline structure with crystallite size of 27.5 nm. The band gap energy of rice leaf biochar (RLB) and Ag@RLEBN was 1.9 and 1.8 eV respectively. Photocatalytic degradation of 99.7% was obtained at initial MB concentration of 0.0001M, 5 mg of Ag@RLEBN and 60 min exposure to sunlight. The main mechanism in control of the degradation of MB was electrostatic attraction, complexation, cationic exchange, ???, n??, and hydrogen bonding. Accessing the reusability of Ag@RLEBN indicated less than 2.05% degradation efficiency disparity after five cycle reuse. The Ag@RLEBN showed high antimicrobial inhibition effectiveness against salmonella (10 nm), Klebsiella (12 nm) and staph aureus (8nm). Therefore, Ag@RLEBN is effective for the removal of MB and microbial decontamination.